Analisis Muatan Life Skill dalam Program Komputer di LKP Karya Prima - Jubaidah Hasibuan; Desi Siahaan; Hangelika Oktavia; Marisa Nabila; Nadia Hani; Putri Pebrija; Sondang Pane; Yolanda Pricilia; Atsylah Nadiva (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
This study aims to analyze the content of life skills in life skills training activities at LKP Karya Prima. The method used is descriptive quantitative with data collection through closed questionnaires given to 20 active training participants. Data analysis was carried out using percentage techniques to identify the proportion of each life skills indicator. The results showed that vocational skills were the most dominant aspect with a percentage of 31%, followed by personal skills at 24%, academic skills at 23%, and social skills at 22%. This finding shows that the development of life skills at LKP Karya Prima emphasizes vocational skills, but still pays attention to personal, academic, and social aspects in a balanced manner. The four indicators complement each other in forming the participants' life skills as a whole